2005
DOI: 10.1002/hep.20673
|View full text |Cite
|
Sign up to set email alerts
|

Activity of CYP2E1 and CYP3A enzymes in adults with moderate alcohol consumption: A comparison with nonalcoholics

Abstract: Alcohol consumption is known to induce hepatic CYP2E1 activity, but its effect on hepatic and intestinal CYP3A in humans is not known. We have conducted a study to compare the CYP2E1 and CYP3A activities in 20 individuals with moderate alcohol consumption and 20 gender-, race-. and body mass index (BMI)-matched nonalcoholics. Intravenous and oral midazolam (MDZ) clearances were used to measure the in vivo CYP3A activity, and chlorzoxazone (CHZ) oral clearance was used to assess in vivo CYP2E1 activity. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…CYP3A4 but not CYP3A5 expression appeared to be upregulated in the frontal cortex of human alcoholic brain. Previous studies suggested that CYP3A expression is induced by ethanol in liver in vivo and ex vivo in primary hepatocytes (Hoshino and Kawasaki, 1995;Kostrubsky et al, 1995) and in the intestine of moderate alcohol consumers (Liangpunsakul et al, 2005). However, to our knowledge, this is the first report of induction of CYP3A by alcohol in the human brain.…”
Section: Discussionmentioning
confidence: 55%
“…CYP3A4 but not CYP3A5 expression appeared to be upregulated in the frontal cortex of human alcoholic brain. Previous studies suggested that CYP3A expression is induced by ethanol in liver in vivo and ex vivo in primary hepatocytes (Hoshino and Kawasaki, 1995;Kostrubsky et al, 1995) and in the intestine of moderate alcohol consumers (Liangpunsakul et al, 2005). However, to our knowledge, this is the first report of induction of CYP3A by alcohol in the human brain.…”
Section: Discussionmentioning
confidence: 55%
“…The ability of alcohol to induce CYP3A in humans is weaker. A recent study indicates that individuals consuming moderate amounts of alcohol have no alteration in hepatic CYP3A activity but reduced midazolam oral bioavailability, possibly as the result of intestinal CYP3A induction (Liangpunsakul et al, 2005). In our study, moderate to heavy chronic alcohol consumption (defined as 14 or more drinks per week) was associated with a small but discernible increase in hepatic CYP3A activity.…”
Section: Pharmacogenetics Of Cyp3a4 and Cyp3a5supporting
confidence: 45%
“…It is possible that it may have taken 4 weeks of alcohol consumption to induce other forms of cytochrome P450 that catalyze the 6-hydroxylation of chlorzoxazone, possibly CYP3A (Gorski et al, 1997). However, in one uncontrolled study, moderate alcohol consumption did not increase CYP3A activity (Liangpunsakul et al, 2005).…”
Section: Figmentioning
confidence: 97%